1997
DOI: 10.1183/09031936.97.10010088
|View full text |Cite
|
Sign up to set email alerts
|

Low diagnostic value of respiratory impedance measurements in children

Abstract: The aim of this study was to determine whether impedance values in children with various chronic respiratory complaints differed from those observed in symptom-free children.Respiratory impedance was measured using the forced oscillation technique in 1,776 Dutch children aged 6-12 yrs. In addition to the commonly used parameters of resistance and reactance, further impedance parameters were obtained by using linear and quadratic regression to describe individual resistance and reactance curves as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
(28 reference statements)
0
13
1
Order By: Relevance
“…The sensitivity and specificity values were calculated from these z-scores and utilised to construct the curve. The line of identity (---) shows the area of the curve where the diagnostic ability is 50% and therefore equal to chance correlation between FOT results and physiological data, in conjunction with the low diagnostic ability observed in our study, brings into question the clinical worth of using FOT in cystic fibrosis despite finding that some outcomes can differentiate between health and the disease.Previous analysis using ROC curves by Cuijpers et al, suggestedthat FOT does not have the ability to detect between health and disease 25. In contrast, our data suggests that FOT can identify between health and disease, though the ability of specific FOT outcomes to detect differences depended on the respiratory disease in question.These opposing findings are likely due to our study stratifying children by specific lung disease, whereas the previous analysis did not classify by respiratory disease and instead compared symptomatic versus asymptomatic children with no formal respiratory diagnosis.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…The sensitivity and specificity values were calculated from these z-scores and utilised to construct the curve. The line of identity (---) shows the area of the curve where the diagnostic ability is 50% and therefore equal to chance correlation between FOT results and physiological data, in conjunction with the low diagnostic ability observed in our study, brings into question the clinical worth of using FOT in cystic fibrosis despite finding that some outcomes can differentiate between health and the disease.Previous analysis using ROC curves by Cuijpers et al, suggestedthat FOT does not have the ability to detect between health and disease 25. In contrast, our data suggests that FOT can identify between health and disease, though the ability of specific FOT outcomes to detect differences depended on the respiratory disease in question.These opposing findings are likely due to our study stratifying children by specific lung disease, whereas the previous analysis did not classify by respiratory disease and instead compared symptomatic versus asymptomatic children with no formal respiratory diagnosis.…”
contrasting
confidence: 77%
“…Previous analysis using ROC curves by Cuijpers et al, suggested that FOT does not have the ability to detect between health and disease . In contrast, our data suggests that FOT can identify between health and disease, though the ability of specific FOT outcomes to detect differences depended on the respiratory disease in question.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory resistance is assumed to reflect airway calibre; therefore, FOT measurements have been employed widely in paediatric studies in various groups of patients with respiratory disease. [23][24][25][26][27][28] While some of these studies suggested that, similarly to other methods, such as spirometry 5 7 and multiple breath washout 29 30 the FOT was able to distinguish between healthy and diseased subject groups, 25 28 31-33 others raised concerns about the diagnostic value of the Zrs data, especially in young children. 23 24 26 27 34 The controversies surrounding the FOT arise from the diversity of Zrs measures reported from the various studies and also from the wide range of the normal values in the paediatric population for any given age or height.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence of disparity between impedance oscillometry measures and spirometry measures of response during bronchial challenge, which may relate to the population being studied 13 . As a single measurement of airway function, resistance and reactance have been found to differ between groups of children defined by an absence or presence of wheeze or cough, 20,21 although this is not a consistent finding 22 . Differences in impedance parameters have been reported from children with cystic fibrosis or neonatal chronic lung disease 23,24 although again, there is a high degree of overlap in impedance parameters between disease and normality.…”
Section: Impedance Oscillometrymentioning
confidence: 99%